2015
DOI: 10.1371/journal.pone.0139677
|View full text |Cite
|
Sign up to set email alerts
|

The Virological and Immunological Characteristics of the HIV-1-Infected Population in Brazil: From Initial Diagnosis to Impact of Antiretroviral Use

Abstract: BackgroundImmunological and virological status of HIV-infected individuals entering the Brazilian public system over time was analyzed. We evaluated the impact of ART on virological, immunological and antiretroviral resistance over time.MethodsCD4+ T cell counts, viral loads and genotypes from patients over 13 years old from 2001–2011 were analyzed according to demographic data. We compared groups using parametric t-tests and linear regression analysis in the R statistical software language.ResultsMean baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
9
15
1
Order By: Relevance
“…However, we believe that our findings portray a realistic clinical picture amidst operational treatment challenges in health care facilities. Our findings further contribute to the body of evidence that consistently good adherence (≥95%) and WHO clinical stage at baseline influence the virological outcomes of patients [27, 35]. Findings seen in our study regarding the contribution of baseline weight on clinical improvement among HIV patients has also been shown elsewhere [37].…”
Section: Discussionsupporting
confidence: 87%
“…However, we believe that our findings portray a realistic clinical picture amidst operational treatment challenges in health care facilities. Our findings further contribute to the body of evidence that consistently good adherence (≥95%) and WHO clinical stage at baseline influence the virological outcomes of patients [27, 35]. Findings seen in our study regarding the contribution of baseline weight on clinical improvement among HIV patients has also been shown elsewhere [37].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of ADRM here detected in Roraima (28%) was relatively low compared to the higher levels of resistance to NRTI, NNRTI and/or PI (>80%) reported in other Brazilian states from all country regions [1119]. It could be argued that most previous studies of ADRM conducted in Brazil analyzed populations of HIV-1-infected individuals failing ART and that the relative low rate of ADRM observed in Roraima may be explained by a low frequency of virological failure among treated patients.…”
Section: Discussionmentioning
confidence: 64%
“…This CRF was more present in the southern region; however, we encountered them throughout the central‐west and southeast regions as well. According to predictions using the Bayesian Markov chain Monte Carlo (MCMC) methods and the reversible‐jump MCMC method, HIV‐1 subtype B emerged in 1971, subtype F emerged in 1981, BF recombinants emerged in 1989, subtype C emerged in 1987 and BC recombinants emerged in 1992 . This study also predicted that the basic reproductive number of secondary infections ( R 0 = 5 year interval) is 2.4 for Brazilian subtype B strains, 2.3 for subtype F and 4.6 for subtype C, warning for the faster expansion of this latter in the Brazilian epidemics .…”
Section: Discussionmentioning
confidence: 83%
“…According to predictions using the Bayesian Markov chain Monte Carlo (MCMC) methods and the reversible‐jump MCMC method, HIV‐1 subtype B emerged in 1971, subtype F emerged in 1981, BF recombinants emerged in 1989, subtype C emerged in 1987 and BC recombinants emerged in 1992 . This study also predicted that the basic reproductive number of secondary infections ( R 0 = 5 year interval) is 2.4 for Brazilian subtype B strains, 2.3 for subtype F and 4.6 for subtype C, warning for the faster expansion of this latter in the Brazilian epidemics . It is also worth mentioning, that one study analysing phenotypic resistance in a limited number of samples from antiretroviral‐naive individuals in Brazil revealed that some subtype C strains presented phenotypic resistance no NRTIs and more frequently to NNRTIs without significant genotypic mutations, which suggests that the genotypic correlates of subtype C resistance might not yet be clearly defined, posing an additional problem related to the HIV‐1 genetic diversity .…”
Section: Discussionmentioning
confidence: 83%